3P (Propel, Plunge, Portray): A Reflective Analysis Of The Accountant's Role In Embedding Sustainability In MSMEs - Ika wahyuni, Nining; Ganis Sukoharsono, Eko; Roekhudin; Baridwan, Zaki (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This research aims to construct the role of accountants in embedding sustainable business practices in MSMEs. Methodology/approach: In constructing the role, the researcher used a participatory action research (PAR) approach. To represent various types of accounting professions, this study used accountant educators as participants. Data were collected through observations, interviews, and group discussion forums. After going through a triangulation process to check its validity, the data was then processed by thematic analysis. Findings: This research successfully constructs the role of accountants in instilling sustainable business practices consisting of three role pillars, namely 3P: propel, plunge, and portray. The three pillars mean that the accountant is a figure capable of being a propel to move every business towards more sustainable conditions. Accountants can act as sustainability change agents by plunging directly into business practices to motivate, facilitate and initiate sustainable business practices. Accountants are also someone who can portray sustainable business practices carried out by a business entity by acting as a preparer of sustainability reports. Practical implications: The results of this study suggest that with this triple role, accountants can further increase their contribution in assisting business entities in implementing the triple bottom line. Originality/value: The research uses an action research approach in the field of sustainability accounting.